Studenttext
Studenttext
Studenttext
Content:
are called quadratic equations. Many can be solved using factorisation. If a quadratic
equation can be written as
( x − a) ( x − b) = 0
then the equation will be satisfied if either bracket is equal to zero. That is,
( x − a) = 0 or ( x − b) = 0
Worked Example 1
Solve x 2 + 6 x + 5 = 0 .
Solution
Factorising gives
( x + 5) ( x + 1) = 0
So
x+5 = 0 or x +1 = 0
therefore
x = −5 or x = −1
Worked Example 2
Solve x 2 + 5 x − 14 = 0 .
Solution
Factorising gives
( x − 2) ( x + 7) = 0
So
x−2 = 0 or x+7 = 0
therefore
x = 2 or x = −7
Worked Example 3
Solve x 2 − 12 x = 0 .
Solution
Factorising gives
x ( x − 12) = 0
So
x = 0 or x − 12 = 0
therefore
x = 0 or x = 12
Worked Example 4
Solve
4 x 2 − 81 = 0
Solution
Factorising gives
( 2 x − 9) ( 2 x + 9) = 0
So
2x − 9 = 0 or 2x + 9 = 0
therefore
9 9
x = or x = −
2 2
1 1
= 4 = −4
2 2
Worked Example 5
Solve x 2 − 4 x + 4 = 0 .
Solution
Factorising gives
( x − 2) ( x − 2) = 0
So
x−2 = 0 or x−2 = 0
therefore
x = 2 or x = 2
This type of solution is often called a repeated solution and results from solving a perfect
square, that is
( x − 2 )2 = 0
Most of these examples have had two solutions, but the last example had only one
solution.
y = x2 + 6x + 5 and y = x 2 − 4 x + 4.
y y
x x
−5 −1 2
The curve crosses the x-axis at The curve touches the x-axis at
x = − 5 and x = −1. x=2
These are the solutions of This is the solution of
2
x + 6x + 5 = 0 x2 − 4x + 4 = 0
Exercises
1. Solve the following quadratic equations.
2. The equations of a number of curves are given below. Find where each curve
crosses the x-axis and use this to draw a sketch of the curve.
(a) y = x2 + 6x + 9 (b) y = x2 − 4
(c) y = 2 x 2 − 3x (d) y = x 2 + x − 12
3. Use the difference of two squares result to solve the following equations.
x+2 x+4
(c) (d)
2x − 3 Area = 45 x +6 Area = 224
2x + 1 2x
5. The height of a ball thrown straight up from the ground into the air at time, t, is
given by
h = 8 t − 10t 2
Find the time it takes for the ball to go up and fall back to ground level.
A = 2GL + 2 EL + W ( E + R)
Theorem
The solutions of the quadratic equation
ax 2 + bx + c = 0
are given by
−b ± b 2 − 4 ac
x =
2a
Proof
The equation ax 2 + bx + c = 0 is first divided by the non-zero constant, a, giving
b c
x2 + x+ = 0
a a
Note that
2
⎛x + b ⎞ = ⎛x +
b ⎞⎛
x+
b⎞
⎝ 2a ⎠ ⎝ 2a ⎠ ⎝ 2a ⎠
2
bx bx ⎛ b ⎞
= x2 + + + (expanding)
2a 2a ⎝ 2a ⎠
2
2 bx ⎛ b ⎞
= x2 + + (adding like terms)
2a ⎝ 2a ⎠
2
bx ⎛ b ⎞
= x2 + + (simplifying)
a ⎝ 2a ⎠
The first two terms are identical to the first two terms in our equation, so you can re-write
the equation as
2 2
⎛x + b ⎞ − ⎛ b ⎞ + c = 0
⎝ 2a ⎠ ⎝ 2a ⎠ a
2 2
⎛x + b ⎞ = ⎛ b ⎞ − c
⎝ 2a ⎠ ⎝ 2a ⎠ a
b2 c
= 2 −
4a a
2
⎛x + b ⎞ b 2 − 4 ac
i.e. =
⎝ 2a ⎠ 4a2
b b 2 − 4 ac
x+ = ±
2a 4a2
± b 2 − 4 ac
=
2a
Hence
b b 2 − 4 ac
x = − ±
2a 2a
−b ± b 2 − 4 ac
or x =
2a
as required.
Worked Example 1
Solve
x2 + 6x − 8 = 0
giving the solution correct to 2 decimal places.
Solution
Here a = 1, b = 6 and c = − 8 . These values can be substituted into
−b ± b 2 − 4 ac
x =
2a
to give
−6 ± 6 2 − ( 4 × 1 × − 8)
x =
2 ×1
− 6 ± 68
=
2
− 6 + 68 − 6 − 68
= or
2 2
= 1.12 or − 7.12 (to 2 d.p.)
Worked Example 2
Solve the quadratic equation
4 x 2 − 12 x + 9 = 0 .
Solution
Here a = 4 , b = −12 and c = 9 . Substituting the values into
−b ± b 2 − 4 ac
x =
2a
gives
12 ± (− 12)2 − (4 × 4 × 9)
x =
2×4
12 ± 144 − 144
=
8
12 ± 0
=
8
12 ⎛ = 3⎞
=
8 ⎝ 2⎠
= 1.5
Worked Example 3
Solve the quadratic equation
x2 + x + 5 = 0
Solution
Here a = 1, b = 1 and c = 5 . Substituting the values into the formula gives
−1 ± 12 − ( 4 × 1 × 5)
x =
2 ×1
−1 ± 1 − 20
=
2
−1 ± − 19
=
2
These three examples illustrate that a quadratic equation can have 2, 1 or 0 solutions.
The graphs below illustrate these graphically and show how the number of solutions
( )
depends on the sign of b 2 − 4 ac which is part of the quadratic formula.
y y y
x
x
xx x x
Exercises
1. Use the quadratic equation formula to find the solutions, where they exist, of each
of the following equations. Give answers to 2 decimal places.
2. A ticket printing and cutting machine cuts rectangular cards which are 2 cm longer
than they are wide.
(a) If x is the width of a ticket, find an expression for the area of the ticket.
3. A window manufacturer makes a range of windows for which the height is 0.5 m
greater than the width.
Find the width and height of a window with an area of 2 m 2 .
h = 20 t − 9.8t 2
where t is the time after the moment of launching.
(a) Find when the stone hits the ground.
(b) For how long is the stone more than 5 m above the ground?
(c) Is the stone ever more than 12 m above ground level?
(d) If m is the maximum height of the stone, write down a quadratic equation
which involves m. Explain why this equation has only one solution and use
this fact to find the value of m, to 2 decimal places.
5. The equation below is used to find the maximum amount, x, which a bungee cord
stretches during a bungee jump:
mgx + mgl − 12 kx 2 = 0 ,
where m = mass of bungee jumper
l = length of rope when not stretched (10 m)
k = stiffness constant (120 Nm ) −1
(a) Find the maximum amount that the cord stretches for a bungee jumper of
mass 60 kg.
(b) How much more would the cord stretch for a person of mass 70 kg?
Solution
First consider the x 2 + 10 x . These terms can be obtained by expanding ( x + 5)2 .
But ( x + 5)2 = x 2 + 10 x + 25
so x 2 + 10 x = ( x + 5)2 − 25
Therefore x 2 + 10 x + 2 = ( x + 5)2 − 25 + 2
= ( x + 5)2 − 23
Worked Example 2
Complete the square for x 2 + 6 x − 8 .
Solution
2
To obtain x 2 + 6 x requires expanding ( x + 3) .
But ( x + 3)2 = x2 + 6x + 9
2
so x 2 + 6 x = ( x + 3) − 9
Therefore x2 + 6x − 8 = ( x + 3)2 − 9 − 8
2
= ( x + 3) − 17
Note
When completing the square for x 2 + bx + c , the result is
2
b b2
x 2 + bx + c = ⎛ x + ⎞ − +c
⎝ 2⎠ 4
2
and for a ≠ 0 , 2 ⎛ b⎞ b2
ax + b x + c = a ⎜ x + ⎟ − +c
⎝ 2a ⎠ 4a
Worked Example 3
Complete the square for 3 x 2 + 6 x + 7 .
Solution
As a first step, the quadratic can be rearranged as shown below.
(
3x 2 + 6 x + 7 = 3 x 2 + 2 x + 7 )
Then note that x2 + 2x = ( x + 1)2 − 1
so ( ) [
3 x 2 + 2 x + 7 = 3 ( x + 1) − 1 + 7
2
]
2
= 3 ( x + 1) − 3 + 7
2
= 3 ( x + 1) + 4
Worked Example 4
(a) Complete the square for y = 2 x 2 − 8 x + 2 .
(b) Find the minimum value of y.
Solution
(a) First rearrange the quadratic as shown.
(
2 x 2 − 8x + 2 = 2 x 2 − 4 x + 2 . )
Then x 2 − 4 x can be written as ( x − 2 )2 − 4 to give
( ) [
2 x 2 − 4 x + 2 = 2 ( x − 2) − 4 + 2
2
]
2
= 2 ( x − 2) − 8 + 2
2
= 2 ( x − 2) − 6
2
(b) As y = 2 ( x − 2) − 6 , the minimum possible value of y is − 6 , which is
obtained when x − 2 = 0 or x = 2 .
(c) Before sketching the graph, it is also useful to find where the curve crosses the
x-axis, that is when y = 0 . To do this, solve
2
0 = 2 ( x − 2) − 6
2
2 ( x − 2) = 6
( x − 2 )2 = 3
x−2 = ± 3
x = 2± 3
y
So the curve crosses the x-axis at 2 + 3
and 2 − 3 , and has a minimum at 6
(2, − 6) .
4
–4
–6
(2, − 6)
Worked Example 5
2
(a) Express 3 x 2 + 2 x + 1 in the form a ( x + p) + q where a, p and q are real
numbers.
Solution
(a) 3 x 2 + 2 x + 1 = a ( x + p) 2 + q
( )
= a x 2 + 2 px + p 2 + q
(
= ax 2 + 2 a px + a p 2 + q )
Equating coefficients:
[x ]
2
3 = a ⇒ a=3
2 1
[ x] 2 = 2a p ⇒ p = =
2a 3
2
1
[c ]
t
1 = a p2 + q = 3 × ⎛ ⎞ + q
⎝ 3⎠
1
= +q
3
1 2
q = 1 − =
3 3
Thus
2
1 2
3x 2 + 2 x + 1 = 3 ⎛ x + ⎞ +
⎝ 3 ⎠ 3
1
(b) (i) Minimum value of y = 3 x 2 + 2 x + 1 will occur when x + = 0 ; that is,
3
1 2
x = − , and the value is y = .
3 3
(ii) y
1
x=− is the equation of the
3
axis of symmetry.
2
3
1 x
−
3
Exercises
1. Complete the square for each of the expressions below.
2. Use the completing the square method to solve each of the following equations.
5. Sketch the graph of each equation below, showing its minimum or maximum point
and where it crosses the x-axis.
(a) y = x2 − 2x − 1 (b) y = x2 + 6x + 8
(c) y = x 2 − 10 x + 24 (d) y = x 2 + 5 x − 14
(e) y = 4 + 3x − x 2 (f) y = 3x − 2 − x 2
h = 1 + 20t − 10t 2
Find the maximum height reached by the ball.
x2 − 4x + 2
2
in the form ( x + a) + b , find a and b and hence find the minimum value
of the expression.
Information
The word 'quadratic' comes from the Latin word 'quadratum', which means 'a squared
figure'.